Diseño del centro de desarrollo comunitario en la Unidad de Planeamiento Zonal (UPZ) San Francisco, Bogotá, Colombia (2021)
The present research work aims to design a community development center in the San Francisco Zonal Planning Unit (UPZ) belonging to the town of Ciudad Bolívar in Bogotá, thus seeking to improve the training and integration conditions of the sector, given the current identified problem of deficit existing in the place and specific problems of a social nature, the methodology used for the development of the research proposes the compilation of information from different structures and city data that, with their subsequent crossing, the problems that they are made possible to solve through architecture, and in the qualitative field with data provided given the immersion in the place of study.